PO 116 - THIRTY-DAY MORBIMORTALITY OF PATIENTS ADMITTED IN AN ACADEMIC MEDICAL CENTRE PACU - ´Rouxinol Dias, Ana Lídia; Rodrigues, Diana; Ferreira, Leonardo; Lima, Ana Patrícia; Ramos, Patrícia; Santos, Alice (Journal of the Portuguese Society of Anesthesiology, 2023)
x